ANALISA KELAYAKAN BEJANA BERTEKANAN TIPE VERTIKAL DENGAN MENGGUNAKAN SIMULASI AUTODESK INVENTOR (Energy, Materials and Product Design, 2022)
The minimum thickness of vertical type pressure vessel of column type distillation, must be planned in accordance with the recommended code of ASME (The American Society of Mechanical Engineering) VIII Div 1. Based on this code, the study aims to determine the feasibility of a pressure vessel that used by PT Pertamina (Persero). For this reason, and to be able to use this ASME code, various data was needed, especially the data sheets and some required data from the field. Based on the data that has been collected, it is then processed and was made a 3D modeling and was simulated using Autodesk Inventor software to test its feasibility. Based on the results of the study, the minimum thickness was obtained, namely head 13.66 mm, shell 13.69 mm, and skirt 3.47 mm, respectively. Taking into account the availability of materials on the market, namely SA-516 Grade 70, the recommended thickness of the head and shell sections was 14 and 5 mm, respectively. From the results of the safety analysis, it was found that at the stress of 0.217, 0.197, 0.196, and 0.195 MPa, the Von Mises stress that occurred ware 0.249; 0.226, 0.225 and 0.224 MPa. From these data, based on the distortion energy failure theory, the head and shell materials which have yield strength of 260 MPa can be categorized as very safe because it does not exceed the yield strength of the material used.